Composition for repair and regeneration of calcified tissue - Patents.com
By using high-concentration collagen particles and biosimilar calcium phosphate materials, the problem of insufficient biocompatibility and self-assembly capability of fracture repair materials in the prior art is solved, and rapid and effective bone regeneration and repair effects are achieved.
Patent Information
- Application Number
- JP2024556321
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-23
- Publication Date
- 2025-04-14
AI Technical Summary
The prior art has limited biocompatibility, self-assembly capability and bone superstructure replication capability in fracture repair and bone regeneration, resulting in poor fracture repair results and often requires multiple surgeries, increasing the burden on patients.
High concentration of collagen particles (more than 90% collagen content) is used to combine biocompatible aqueous solvents with biosimilar calcium phosphate or its precursors to form biosimilar bone repair materials that can be injected or implanted.
The biocompatibility and self-assembly capability of bone repair materials is achieved, and it can quickly regenerate bone tissue, reduce the number of surgeries, and improve the fracture repair effect.
Smart Images

Figure 2025510075000001 
Figure 2025510075000002 
Figure 2025510075000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of repair and regeneration of mineralized biological tissues. In particular, the present invention relates to injectable or implantable compositions capable of mimicking different types of mineralized biological tissues and their use in repair and regeneration of mineralized tissues (e.g. bone). [Background technology]
[0002] Bone is a composite tissue. The extracellular matrix (ECM) of bone is composed of a mineral phase (about 65% by weight), an organic phase (roughly 25% by weight) with type I collagen as the main component, and water (about 10% by weight). This ECM is continuously regenerated and remodeled, allowing the repair of small defects (such as microfractures) and the mechanical adaptation of the tissue. However, if the defect is too large, it can no longer be resorbed by cellular processes (Schmitz, JP and JO Ollinger. 1986. "The Critical Size Defect as an Experimental Model for Craniomandibulofacial Nonunions." Clinical Orthopaedics and Related Research NO. 205: 299-308). A scaffold (support) is then needed to facilitate bone repair. Ideally, the scaffold has the same properties (composition, ultrastructure, mechanical properties) as bone tissue.
[0003] Bone autografts remain the gold standard for bone grafting (Bauer, Thomas W. and George F. Muschler. 2000. "Bone Graft Materials." Clinical Orthopaedics and Related Research 371:10-27). However, bone autograft materials have several drawbacks, including limited availability and the need to perform additional surgery, which may worsen the patient's condition. To limit the invasiveness of the two-stage surgical procedure, injectable composite materials for bone regeneration have been proposed, such as hydroxyapatite microparticles coated with low-concentration collagen (Flautre, B. et al. (1996) "Evaluation of hydroxyapatite powder coated with collagen as an injectable bone substitute: Microscopic study in rabbit", Journal of Materials Science: Materials in Medicine, 7(2), pp. 63-67) or mineralized low-concentration collagen microspheres (Yin Hsu, F., Chueh, S. C. and Jiin Wang, Y. (1999) "Microspheres of hydroxyapatite / reconstituted collagen as supports for osteoblast cell growth", Biomaterials, 20(20), pp. 1931-1936).However, these methods require a systematic chemical crosslinking step because the low collagen concentration makes the microspheres fragile, which can lead to inflammation and poor biological responses, such as osseointegration (Speer, DP, Chvapil, M., Eskelson, C. & Ulreich, J. Biological effects of residual glutaraldehyde in glutaraldehyde-tanned collagen biomaterials. J. Biomed. Mater. Res. 14, 753-764 (1980); Bellincampi, LD & Dunn, MG Effect of crosslinking method on collagen fiber-fibroblast interactions. J. Appl. Polym. Sci. 63, 1493-1498 (1997)). Another strategy consists in mineralizing collagen fibrils to form an injectable paste (Liu, X. et al. (2010) "Injectable bone cement based on mineralized collagen", Journal of Biomedical Materials Research-Part B Applied Biomaterials, 94(1), pp. 72-79; Pelin, I. M. et al. (2009) "Preparation and characterization of a hydroxyapatite-collagen composite as component for injectable bone substitute", Materials Science and Engineering C. Elsevier BV, 29(7), pp. 2188-2194).Here again, low concentrations of collagen are used which prevent the formation of bone-like 3D constructs because the threshold for collagen self-organization is not reached (Giraud-Guille, Marie Madeleine. 1992. "Liquid Crystallinity in Condensed Type I Collagen Solutions. A Clue to the Packing of Collagen in Extracellular Matrices." Journal of Molecular Biology 224(3):861-73; Giraud-Guille, Marie Madeleine and Laurence Besseau. 1998. "Banded Patterns in Liquid Crystalline Phases of Type I Collagen: Relationship with Crimp Morphology in Connective Tissue Architecture." Connective Tissue Research 37(3-4):183-93).In addition, none of the cited studies have demonstrated any significant differences in composition, structure, morphology, size (Nassif, N., F. Martineau, O. Syzgantseva, F. Gobeaux, M. Willinger, T. Coradin, S. Cassaignon, T. Azais, and M. M. Giraud-Guille. 2010. “In Vivo Inspired Conditions to Synthesize Biomimetic Hydroxyapatite.” Chemistry of Materials 22(12):3653-63) and properties upon hydration (Wang, Yan, Stanislas Von Euw, Francisco M. Fernandes, Sophie Cassaignon, Mohamed Selmane, Guillaume Laurent, Gerard Pehau-Arnaudet, Cristina Coelho, Laure Bonhomme-Coury, Marie Madeleine Giraud-Guille, Florence Babonneau, Thierry Azais, and Nadine Nassif. 2013. "Water-Mediated Structuring of Bone Apatite." Nature Materials 12(12):1144-53) have not used biomimetic hydroxyapatite. Other formulations containing additives have been proposed to improve the mechanical properties of such biomaterials, i.e., adhesion and handling, for easier application in defects (Chen, Z. et al. (2011) "Injectable calcium sulfate / mineralized collagen-based bone repair materials with regulable self-setting properties", Journal of Biomedical Materials Research-Part A, 99 A(4), pp. 554-563; Huang, Z. et al. (2009) "A bone-like nano-hydroxyapatite / collagen loaded injectable scaffold", Biomedical Materials, 4(5)).They allow good injectability of the biomaterials and in situ gelation, allowing filling of defects within a short period of time. Nevertheless, the composition of such materials is not biomimetic, thereby preventing the regeneration of bone ultrastructure.
[0004] In fact, 3D organization of dense collagen materials appears to be a prerequisite for mimicking the ultrastructure of living tissues, especially the twisted plywood found in bone (Wang, Y. et al. (2011) "Controlled collagen assembly to build dense tissue-like materials for tissue engineering", Soft Matter, 7(20), pp. 9659-9664), and for promoting colonization by host cells. Such fibrillar collagen matrices also show improved mechanical properties without the need for additives or crosslinkers (Lama, M, et al. "Biomimetic Tough Gels with Weak Bonds Unravel the Role of Collagen from Fibril to Suprafibrillar Self-Assembly." Macromolecular Bioscience 21.6(2021):2000435). Previous studies have shown that mineralization of high-concentration collagen matrices promotes both the formation of biomimetic hydroxyapatite nanoplatelets and their co-alignment with collagen fibrils (Wang, Y. et al. (2012) "The predominant role of collagen in the nucleation, growth, structure and orientation of bone apatite." Nature materials. Nature Publishing Group, 11(8), pp. 724-33.). Even though such matrices are less mineralized than native bone tissue, this degree of order has been shown to result in stiffness reaching gigapascals (Nassif, N. et al. (2010) "In vivo inspired conditions to synthesize biomimetic hydroxyapatite." Chemistry of Materials, 22(12), pp. 3653-3663), thus stimulating interest in processing high collagen concentrates. However, such preformed collagen matrices are not injectable. Summary of the Invention
[0005] Therefore, there remains a need for injectable or implantable compositions that overcome one or more of the above-mentioned drawbacks, in particular for injectable or implantable compositions that are able to mimic different types of mineralized biological tissue, in particular bone, that exhibit good adhesion and cohesion to the defect to be repaired, and that allow rapid regeneration of mineralized tissue.
[0006] The present invention relates to - collagen microparticles containing more than 90% by weight of collagen; - biomimetic hydroxyapatite or biomimetic hydroxyapatite precursor or amorphous calcium phosphate; and - Physiologically compatible aqueous solvent The present invention relates to a composition comprising:
[0007] The present invention also relates to the compositions defined herein for use in the repair and regeneration of mineralized tissue to induce new bone formation, promote bone growth and / or treat bone defects, as well as for use in bone reconstruction procedures, preferably in the repair of bone defects in maxillofacial or orthopedic surgery.
[0008] The present invention also relates to preformed implantable matrices comprising the compositions described herein.
[0009] The present invention also relates to processes as defined in claims 13, 14 and 15 for preparing the compositions described herein.
[0010] Further aspects of the invention are disclosed herein and in the claims. [Brief description of the drawings]
[0011] [Figure 1]FIG. 13 is a TGA thermogram of a composite collagen material showing good agreement between the initial weight (collagen microparticles contain approximately 10% water by weight) and the measured organic and inorganic components (initial collagen / hydroxyapatite ratio 1:1). [Diagram 2] FIG. 14 DSC analysis of different collagen materials prepared in saline, showing similar endothermic peaks typical of collagen denaturation. [Diagram 3] PLM observation of complex collagen solution: bright birefringent structures provide evidence for anisotropic organization. [Figure 4] SEM micrographs of mineralized collagen material showing partially dissolved collagen microparticles before fibrillogenesis (left) After fibrillogenesis (right), the material shows more defined collagen fibrils. [Diagram 5] FIG. 1 is an SEM micrograph of a mineralized collagen gel (collagen / hydroxyapatite ratio 1:1) showing fibrillar aligned domains within a dense matrix. [Figure 6] FIG. 13 is a TEM micrograph of unstained ultrathin sections of collagen / HA50:50 matrices with high dry matter content showing the co-alignment of collagen fibrils and hydroxyapatite nanoplatelets. [Figure 7] Images showing the presence of fibrovascular and leukocyte infiltrate / colony formation within the injectable material fragment. The circles identify the presence of infiltrates / cell colonies within the injectable material fragment (*). (□) Polymorphous inflammatory response with macrophage and multinucleated giant cell components in contact with the material. [Figure 8]Preformed material (Process 2) produced using dense collagen microparticles mixed with a biomimetic hydroxyapatite precursor solution. (a-c) SEM micrographs showing the material exhibits a high density of collagen fibrils. (d) TEM micrograph showing the arrangement of collagen fibrils in the material. (e) Infrared spectra of (i) dense collagen microparticles, (ii) preformable material (Process 2) produced using dense collagen microparticles mixed with a biomimetic hydroxyapatite precursor solution, and (iii) biomimetic apatite (CHA). It can be observed that the preformed material exhibits vibrational bands attributable to both collagen and apatite, thereby supporting the formation of a collagen mineralized matrix. [Figure 9] Composite dense collagen / biomimetic hydroxyapatite precursor microparticles (Process 3). (a) SEM micrograph of the composite dense microparticles. (b) EDX spectra showing the incorporation of biomimetic hydroxyapatite precursor into the dense collagen microparticles. (c-d) SEM micrographs of preformed material produced using the composite dense collagen / biomimetic hydroxyapatite precursor microparticles. Dense fibrils can be observed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The inventors have developed compositions that overcome one or more of the above-mentioned drawbacks. They allow the injection or implantation of mineralized, highly concentrated collagen matrices with bone-like characteristics in terms of composition and ultrastructure. The compositions developed by the inventors are capable of mimicking different types of mineralized living tissues. They preserve collagen self-organization properties and even promote a biomimetic co-assembly of collagen and hydroxyapatite. The compositions are biocompatible and favor the colonization of host cells. They do not cause an inflammatory response.
[0013] Such compositions pave the way for biomimetic and injectable mineralized tissue substitutes such as bone with adaptable composition. They may be used in the field of bone tissue regeneration, offering a promising new therapeutic approach for efficient tissue regeneration.
[0014] The composition developed by the inventors is - high density collagen microparticles (i.e. microparticles containing more than 90% collagen by weight); - biomimetic hydroxyapatite or biomimetic hydroxyapatite precursor or amorphous calcium phosphate; and - Physiologically compatible aqueous solvent Includes.
[0015] The composition is suitable for injection and / or implantation, in which case the composition may be defined as injectable and / or implantable.
[0016] The components of the compositions of the present invention are described in detail herein below.
[0017] The term "injectable" as used herein means the ability to place the material at the desired site using a commercially available syringe with or without a needle.
[0018] The term "implantable" as used herein means an object capable of being implanted into the human body by conventional surgical procedures.
[0019] High-density collagen particles The term "high density collagen microparticles" as used herein means collagen microparticles that contain more than 90% collagen by weight, particularly more than 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% collagen by weight, with the remainder being water.
[0020] High density collagen microparticles are as disclosed in WO2016 / 146954.
[0021] High density collagen microparticles are in the form of solid spherical or spheroidal particles formed of undenatured and uncrosslinked collagen. The diameter of the particles is usually in the range of 0.05-20 μm, in particular 0.25-10 μm, more particularly 0.4 μm-3 μm. It should be understood that the particle size range refers to the diameter distribution. The particles usually have a diameter ranging from a minimum diameter of 0.05 μm to a maximum diameter of 20 μm.
[0022] The term "spheroid" as used herein means a solid whose shape resembles that of a sphere.
[0023] The term "diameter" means the diameter of a sphere or the maximum diameter of a spheroid. Diameter can be measured, for example, by electron microscopy or by dynamic light scattering.
[0024] The term "undenatured" as used herein refers to collagen in which the secondary structure of the alpha triple helix is preserved. The undenatured or denatured nature of collagen can be observed, for example, by calorimetry. Denatured collagen has a calorimetry profile characteristic of denatured protein (gelatin) with no signs of organized polymeric domains.
[0025] The term "non-crosslinked" as used herein means collagen that is free of crosslinks, whether such bonds are the result of chemical or enzymatic or physical modification, such as treatment with glutaraldehyde. The absence of crosslinks can be determined, for example, by electrophoresis.
[0026] High-density collagen microparticles may be prepared from various collagens. The source of collagen is therefore not critical. Collagen can be obtained according to the following protocol: A solution of type I collagen is prepared from Wistar rat tail tendons. After dissection in a laminar flow cabinet, the tendons are washed in sterile phosphate-buffered saline. The tendons are then immersed in a 4M NaCl solution to remove remaining intact cells and to precipitate some of the high molecular weight proteins. After washing with phosphate-buffered saline, the tendons are dissolved in a sterile 500 mM acetic acid solution. The resulting solution is clarified by centrifugation at 41000g for 2 hours. Proteins other than collagen are selectively precipitated in a 300 mM aqueous NaCl solution and removed by centrifugation at 41000g for 3 hours. Collagen is recovered from the supernatant by precipitation in a 600 mM NaCl solution followed by centrifugation at 3000g for 45 minutes. The resulting pellet is dissolved in a 500 mM aqueous acetic acid solution and then dialyzed against the same solvent to remove NaCl ions. The solution is kept at 4 °C and centrifuged at 41,000 g for 4 h before use. This detailed protocol can be applied to other types of collagen.
[0027] The collagen in the high density collagen microparticles typically has a molecular weight in the range of 200-450 kDa.
[0028] The collagen of the high density collagen microparticles is usually collagen type I. Nevertheless, the collagen may alternatively be of types II, III, V, XI, XXIV, XXVII and mixtures thereof.
[0029] The high-density collagen microparticles may be prepared by the spray processing technique disclosed in WO2016 / 146954. Briefly, the spray processing technique consists in atomizing an acid-soluble collagen solution (undenatured and uncrosslinked collagen) to form a very thin mist of droplets, which are quickly dried by solvent evaporation in a controlled atmosphere (due to the large solution / air interfacial area of the droplets). The concentration of collagen in the acidic collagen solution is usually in the range of 0.1-10 mg / L. The acidic collagen solution has a pH of less than 7. The acid is usually acetic acid. The concentration of acetic acid in the acidic collagen solution is usually in the range of 0.1-1000 mM. The atomization is usually carried out at a temperature below about 40° C., in particular below about 39° C., about 38° C. or about 37° C., to obtain a powdered composition. The concentration of collagen droplets is high enough to induce self-organization of collagen molecules and subsequent liquid crystal ordering, e.g., nematic orientation domains. This strategy makes it possible to obtain highly concentrated collagen microparticles within seconds, avoiding the significant increase in viscosity of type I collagen solutions that usually prevents fast processing of this protein, thus enabling its use at biological concentrations.
[0030] Formation of dense collagen microparticles by aerosol (WO2016 / 146954) has previously been shown to enable the injection of highly concentrated collagen gels (at least up to 80 mg / mL) (Milena Lama, Francisco M. Fernandes, Alba Marcellan, Juliette Peltzer, Marina Trouillas, Sebastien Banzet, Marion Grosbot, Clement Sanchez, Marie Madeleine Giraud-Guille, Jean Jacques Lataillade, Bernard Coulomb, Cedric Boissiere, and Nadine Nassif. 2020. "Self-Assembled Collagen Microparticles by Aerosol as a Versatile Platform for Injectable Anisotropic Materials." Small 16(4):1-8). After being injected or placed into a mold (Lama, M. et al. "Biomimetic Tough Gels with Weak Bonds Unravel the Role of Collagen from Fibril to Suprafibrillar Self-Assembly." Macromolecular Bioscience 21.6(2021):2000435), the self-assembled collagen matrices exhibited tissue-like characteristics in terms of both ultrastructural and mechanical properties.
[0031] Biomimetic Hydroxyapatite The term "biomimetic hydroxyapatite" refers to bone-like hydroxyapatite platelets.
[0032] The biomimetic hydroxyapatite is usually in the form of a powder.
[0033] Biomimetic hydroxyapatite powder may be synthesized according to the procedure described by Nassif et al., Chemistry of Materials, 22(12), pp. 3653-3663, 2010. Briefly, biomimetic hydroxyapatite is prepared by vapor diffusion of ammonia (NH3) into an acidic calcium-phosphate (CaCl2-NaH2PO4- or possibly other salts, especially with NaHCO3) solution under thermodynamic conditions to avoid precipitation of other calcium-phosphate phases. For example, biomimetic hydroxyapatite can be prepared by the vapor diffusion of ammonia (NH3) into an acidic calcium-phosphate (CaCl2-NaH2PO4- or possibly other salts, especially with NaHCO3) solution under thermodynamic conditions to avoid precipitation of other calcium-phosphate phases. 10 CaCl2 / NaH2PO4 acidic solution (acetic acid, 500 mM) with a calcium to phosphate (Ca / P) molar ratio consistent with the formation of hydroxyapatite according to the formula (PO4)6(OH2), or Ca 10-x (PO4) 6-x (CO3) x (OH) 2-x It may be prepared by precipitation in an acidic solution of CaCl2 / NaH2PO4 / NaHCO3 (acetic acid, 500 mM) with a calcium to phosphate plus carbonate (Ca / [P+C]) molar ratio consistent with the formation of hydroxyapatite according to the formula 0≦x≦2. Precipitation is induced by the addition of aqueous ammonia (30%, w / w).
[0034] This precipitation method has the advantage of being free of any organic additives, being carried out at room temperature within a few hours without direct pH control, and does not produce any by-products or undesirable (i.e. non-physiological) phases. The synthesis of biomimetic hydroxyapatite disclosed by Nassif et al., 2010, was shown to result in nanoplatelets that exhibit self-organizing properties similar to natural bone apatite in water (Wang, Yan et al. "Water-mediated structuring of bone apatite." Nature materials 12.12 (2013): 1144-1153). The nanoplatelets have been shown to have a crystalline core and an amorphous shell with X-ray diffraction patterns consistent with those of JCPDS N 9-0432. They typically have an average size of 200 × 100 × 5 nm 3 , with carbonate replacement observed in bone mineral.
[0035] It should be noted that the composition of hydroxyapatite may also be modified, particularly enriched in strontium (up to 10% calcium substitution), to combine anti-osteoporotic effects (Tovani et al., “Formation of stable strontium-rich amorphous calcium phosphate: Possible effects on bone mineral,” Acta biomaterialia, 2019).
[0036] Biomimetic hydroxyapatite precursors The term "biomimetic hydroxyapatite precursor" refers to precursor ions that lead to the formation of biomimetic hydroxyapatite under conditions described, for example, in Nassif et al., Chemistry of Materials, 22(12), pp. 3653-3663, 2010.
[0037] Suitable biomimetic hydroxyapatite precursors include CaCl2·2H2O, NaH2PO4 and NaHCO3, as well as salts that may be found in the mineral composition of bone, including salts of magnesium, zinc, fluorite and strontium.
[0038] The Ca / P molar ratio is usually in the range of 1.5-2.
[0039] The calcium to phosphate plus carbonate ratio (Ca / [P+C]) molar ratio is preferably calculated according to the formula Ca 10-x (PO4) 6-x (CO3) x (OH) 2-x , consistent with the formation of hydroxyapatite, with the formula 0≦x≦2 (von euw, scientific report 2019).
[0040] Amorphous calcium phosphate The term "amorphous calcium phosphate" refers to amorphous calcium phosphate particles. Amorphous calcium phosphate is usually in the form of a powder.
[0041] Amorphous calcium phosphate powders may be synthesized by atomization of a biomimetic hydroxyapatite precursor acidic solution using the spray processing technique disclosed in WO2016 / 146954.
[0042] Aqueous Solvent The aqueous solvent may be any physiologically compatible aqueous solvent. Non-limiting examples of suitable aqueous solvents include physiological serum, phosphate buffer, sodium bicarbonate, sterile water, normal saline solution, blood or plasma.
[0043] Optional Therapeutic or Bioactive Agents The compositions may also include one or more therapeutic or bioactive agents, such as anti-inflammatory agents, antibiotics, bone morphogenetic proteins, hyaluronic acid, cells, growth factors, and anti-osteoporotic agents (eg, salts).
[0044] Process for preparing the composition Process 1: Mixing high-density collagen microparticles with hydroxyapatite or amorphous calcium phosphate The composition according to the present invention can be prepared by mixing a desired weight of high density collagen microparticles, usually in powder form, with a desired weight of hydroxyapatite powder or amorphous calcium phosphate powder (Process 1). The high density collagen microparticles and hydroxyapatite or amorphous calcium phosphate powder can be prepared as described herein above. The high density collagen microparticles and hydroxyapatite or amorphous calcium phosphate powder are usually mixed in a mortar. The mixing of the high density collagen microparticles and hydroxyapatite or amorphous calcium phosphate powder is usually performed in a weight ratio appropriately selected to reproduce the target tissue, which can be adapted to the target application. Non-limiting examples of suitable weight ratios of high density collagen microparticles to hydroxyapatite or amorphous calcium phosphate powder include the following ratios: 10:90 to 90:10, preferably 30:70 to 80:20, more preferably 50:50.
[0045] After the high density collagen microparticles and hydroxyapatite or amorphous calcium phosphate powder are mixed in an appropriate weight ratio, the aqueous solvent described herein is added to the mixture. The weight ratio of the aqueous solvent to the mixture of high density collagen microparticles and hydroxyapatite or amorphous calcium phosphate powder is usually 1.8-10 (i.e., in the range of 0.18 mL-1 mL of solvent per 100 mg of the mixture of high density collagen microparticles and hydroxyapatite or amorphous calcium phosphate powder), preferably in the range of 2-9, more preferably in the range of 3-8.
[0046] The mixture may then be supplemented with one or more therapeutic or bioactive agents, such as an anti-inflammatory agent or an anti-osteoporosis agent.
[0047] After mixing, the resulting composition, in paste or liquid form, may be inserted into a sterile syringe.
[0048] All steps of the disclosed processes are preferably performed under sterile conditions.
[0049] The syringe may then be stored in a dry place at a temperature below the denaturation temperature of collagen, preferably in a refrigerator at 4°C.
[0050] Alternatively, the composition may be prepared by atomizing an acidic solution containing the biomimetic hydroxyapatite precursor and undenatured and uncrosslinked collagen (Process 2), or dense collagen microparticles may be mixed with an aqueous solution containing the biomimetic hydroxyapatite precursor (Process 3).
[0051] Process 2: Atomization of biomimetic hydroxyapatite precursor containing collagen solution The compositions according to the invention may be prepared by a process which includes atomizing a solution containing a hydroxyapatite precursor and undenatured and uncrosslinked collagen.
[0052] The spray treatment technique is performed as disclosed in WO2016 / 146954. Atomization is performed with an acid soluble collagen solution (undenatured and uncrosslinked collagen). The concentration of collagen in the acidic collagen solution is typically in the range of 0.1-10 mg / L. The acidic collagen solution has a pH below 7. The acid is typically acetic acid. The concentration of acetic acid in the acidic collagen solution is typically in the range of 0.1-1000 mM. The collagen solution is mixed with a desired volume / concentration of a biomimetic hydroxyapatite precursor solution (i.e. the acidic collagen solution is supplemented with an ionic precursor of hydroxyapatite). In a preferred setup, the biomimetic hydroxyapatite precursor solution is made by dissolving biomimetic hydroxyapatite platelets in an acidic solution.
[0053] Atomization is typically carried out at a temperature below about 40° C., particularly below about 39° C., about 38° C. or about 37° C., to obtain an undenatured powdered composition.
[0054] The resulting microparticles from atomization are referred to herein as "composite dense collagen microparticles". The composite dense collagen microparticles are the dense collagen microparticles disclosed herein above that contain biomimetic hydroxyapatite ionic precursors (e.g., CaCl2·2H2O, NaH2PO4 and NaHCO3). Composite microparticles with different ionic compositions may be obtained. Calcium acetate may be used as an alternative to calcium chloride to avoid NaCl precipitation.
[0055] Mixing of the composite dense collagen microparticles with a physiologically compatible aqueous solvent (with or without a biomimetic hydroxyapatite precursor) is typically performed in a weight ratio appropriately selected to reproduce the target tissue, which can be adapted to the target application.
[0056] After mixing, the resulting composition, in paste or liquid form, may be inserted into a sterile syringe.
[0057] All steps of the disclosed processes are preferably performed under sterile conditions.
[0058] The syringe may then be stored in a dry place at a temperature below the denaturation temperature of collagen, preferably in a refrigerator at 4°C.
[0059] Process 3 : Mixing high-density collagen microparticles with biomimetic hydroxyapatite precursor solutions The composition according to the present invention can be prepared by mixing a desired weight of high density collagen microparticles, usually in powder form, with a desired volume of biomimetic hydroxyapatite precursor solution.The high density collagen microparticles and the biomimetic hydroxyapatite precursor solution can be prepared as described herein above.The high density collagen microparticles and the biomimetic hydroxyapatite precursor solution are usually mixed in a mortar or well.The mixing of the high density collagen microparticles and the biomimetic hydroxyapatite precursor solution is usually performed in a weight ratio appropriately selected to reproduce the target tissue, which can be adapted to the target application.
[0060] The volume of biomimetic hydroxyapatite precursor solution added to the dense collagen microparticles typically results in a final concentration of 80 mg / mL collagen.
[0061] After mixing, the resulting composition, in paste or liquid form, may be inserted into a sterile syringe.
[0062] All steps of the disclosed processes are preferably performed under sterile conditions.
[0063] The syringe may then be stored in a dry place at a temperature below the denaturation temperature of collagen, preferably in a refrigerator at 4°C.
[0064] Compositions and uses thereof The composition of the present invention comprises - high density collagen microparticles (i.e. microparticles containing more than 90% collagen by weight); - biomimetic hydroxyapatite or biomimetic hydroxyapatite precursor or amorphous calcium phosphate; and - Physiologically compatible aqueous solvent Includes.
[0065] When the composition is prepared according to Process 1, the composition of the present invention more specifically comprises: - high density collagen microparticles (i.e. microparticles containing more than 90% collagen by weight); - Biomimetic hydroxyapatite platelets or amorphous calcium phosphate; and - Physiologically compatible aqueous solvent may be defined as including
[0066] When the composition is prepared according to process 2, the composition of the present invention more specifically comprises: - Composite dense collagen microparticles (i.e. dense collagen microparticles containing a biomimetic hydroxyapatite precursor); and - a physiologically compatible aqueous medium, optionally including a biomimetic hydroxyapatite precursor; may be defined as including
[0067] When the composition is prepared according to process 3, the composition of the present invention more specifically comprises: - High density collagen microparticles (i.e. microparticles containing more than 90% collagen by weight); and - A physiologically compatible aqueous medium containing a biomimetic hydroxyapatite precursor may be defined as including
[0068] The composition generally contains 10 mg to 100 mg, preferably 40 mg to 80 mg, and more preferably 50 mg to 70 mg of high-density collagen microparticles per mL of composition.
[0069] In some embodiments, the weight ratio of high density collagen microparticles to biomimetic hydroxyapatite or amorphous calcium phosphate in the composition (which may be prepared according to Process 1) ranges from 10:90 to 90:10, preferably 30:70 to 80:20, and more preferably 50:50.
[0070] Those skilled in the art will easily adjust the weight ratio of the high density collagen microparticles to the biomimetic hydroxyapatite or amorphous calcium phosphate to adapt the composition formulation to the intended application, target mineralized tissue and administration site. Varying the weight ratio of the high density collagen microparticles to the biomimetic hydroxyapatite may result in mineralized collagen matrices with different ultrastructural and mechanical properties.
[0071] The composition of the present invention can be easily implanted or injected or otherwise applied to the site where calcified tissue needs repair. For example, the composition can be suitably injected with a syringe directly into the defect site to be repaired. The composition is capable of filling the target defect and adopting the same 3D shape. The composition is adhesive / tacky enough to be held in the defect site without external assistance or agents.
[0072] Alternatively, the composition may be injected into a mold to form a preformed matrix, which is implantable.
[0073] Due to the properties and ability to mimic different types of mineralized living tissue, the compositions of the present invention may be used for repair and regeneration of mineralized tissue. In particular, the compositions may be used for bone repair and regeneration. They may be used to induce new bone formation, promote bone growth and / or treat bone defects. Various bone defects where new bone formation or growth is required may be treated with the disclosed compositions. More specifically, the compositions of the present invention may be used as bone and / or dental substitutes. For example, the compositions may be used for filling teeth in dental surgery. They may also be used to repair bone defects in bone reconstruction procedures, such as in maxillofacial surgery (reconstruction of the bone arch of the tooth) or in orthopedic surgery, especially vertebroplasty. In these embodiments, the compositions are directly injected into the defect site to be repaired.
[0074] In some embodiments, the present invention relates to a method for regenerating mineralized tissue, inducing new bone formation, promoting bone growth and / or treating bone defects comprising the step of injecting or implanting a composition described herein into an individual in need of such treatment.
[0075] The composition of the present invention may also be used to prepare preformed mineralized collagen matrix, such as preformed bone-like material.For example, the composition may be injected into a mold or used for 3D printing to form a preformed implantable mineralized collagen matrix.The present invention also relates to these preformed implantable matrices.
[0076] The composition promotes biomimetic remineralization of osteoporotic bone and localized Sr 2+ These compositions may be used to induce the delivery of Sr, which can restore the imbalance between bone formation by osteoblasts and bone resorption by osteoclasts, one of the main causes of osteoporosis. For example, composite collagen / CHA ionic precursor microparticles can be injected and induce in situ mineralization after contact with body fluids. Furthermore, the incorporation of Sr into this composition can 2+may be used for the in situ release of this ion, which is normally present in oral formulations for the treatment of osteoporosis, namely strontium ranelate. EXAMPLES
[0077] Embodiments of the present invention will now be described by the following examples, which are provided for illustrative purposes only and are not intended to limit the scope of the disclosure.
[0078] Example 1: Injectable and preformed composites in 0.9% saline (collagen / hydroxyapatite ratio 50:50) Synthesis of carbonated hydroxyapatite The synthesis of carbonated hydroxyapatite was carried out according to the procedure described by Nassif et al. (Chemistry of Materials, 22(12), pp. 3653-3663, 2010).
[0079] A solution of 110 mM CaCl2·2H2O, 33 mM NaH2PO4 and 33 mM NaHCO3 was prepared in 500 mM acetic acid. The pH was adjusted to 2.2 with a 37% HCl solution. Two flasks (35 mL) were filled with 20 mL of this solution and placed in an airtight sealed chamber (i.e. in a 1 L beaker covered with paraffin) in the presence of a third vial containing 8 mL of a 28-30% by mass NH3 aqueous solution. Before closing, these three flasks were covered with parafilm in which six holes were pierced using a needle to slow down the gas diffusion of ammonia. The device was then left for 6 days. The precipitate was then recovered by centrifugation (20 min at 6000 rpm) at room temperature and washed with ultrapure water until the pH of the supernatant approached that of the wash water. The resulting white powder was finally dried in an oven at 37 °C for 7 days. The dried powder was then finely ground with a pestle in a mortar to obtain a fine powder.
[0080] Synthesis of collagen microparticles by aerosol The synthesis of collagen microparticles was carried out according to the procedures described by Nassif et al. (Paris, 2018. Injectable collagen suspensions, the preparation method thereof, and the uses thereof, particularly for forming dense collagen matrices. U.S. Patent Application 15 / 558,787) and Lama et al. (Self-Assembled Collagen Microparticles by Aerosol as a Versatile Platform for Injectable Anisotropic Materials. Small, pp. 1902-224, 2019).
[0081] A collagen solution concentrated to 1.2 mg / mL was obtained by diluting the collagen stock solution (usually 1.3-5 mg / mL) in acetic acid (500 mM). 250 mL of said solution was dried in a spray dryer (Buchi B290). The spray dryer was placed under a fume hood next to a mobile reversible air conditioner. The temperature under the fume hood should ideally be maintained between 19°C and 21°C (not preferred above 25°C). The injection rate of the collagen solution (at 1.2 mg / mL) was controlled by the peristaltic pump of the atomizer and was equal to 0.6 mL / min. The set temperature of the nozzle is maintained at 30°C. The actual temperature of the nozzle varies between 34°C and 35°C after 1 hour of stabilization in the vacuum (before starting the peristaltic pump). The internal temperature of the system, measured between the drying column and the particle recovery cyclone, is between 19°C and 25°C. The airflow, which causes the droplets to be sheared at the nozzle outlet, is 414 L / h. The suction power, which controls the drying of the droplets between the nozzle outlet and the collector, is set at 50% of the maximum capacity of the drying system, i.e. 20 m3 / h. The "nozzle" parameter, which is used to prevent the agglomeration of the solution at the tip of the nozzle, is set at 2. Aluminum is placed at both ends of the junction between the column and the cyclone to avoid heat losses as much as possible. The formed particles are collected by a high-performance cyclone connected to a flask. In order to collect all the powder remaining on the walls of the cyclone and to maximize the yield, the temperature set point is stopped at the end of the atomization and the suction is increased in 10% increments from 50% (20 m3 / h) to 100% (40 m3 / h) by waiting 5 minutes per step. The process efficiency is 50%-60%. To guarantee sterile conditions, commercial devices of different sizes of filters sold by BEKO technologies may be used. It is also recommended to sterilize the entire apparatus with ethanol higher than 94 ° before spraying the collagen.
[0082] Preparation of the injectable composition 60 mg of collagen powder obtained as disclosed herein above and 60 mg of hydroxyapatite powder obtained as disclosed herein were mixed in a mortar. 1 mL of sterile saline (NaCl 0.9%) was added to the mortar. The whole was mixed for about 1 minute to obtain a homogenous paste. The paste was transferred to an empty 1 mL syringe. The plunger was replaced to its original position. The paste was then ready to be injected into the defect.
[0083] Preparation of preformed substrates The above protocol is repeated. The mixture is injected via a syringe into a silicone mold of the desired dimensions and a total volume of 1 mL. Fibril development (gelation) is carried out overnight under ammonia vapor. The gel is then removed from the mold and rinsed with saline until a neutral pH is reached. The material can then be implanted into the void that corresponds to the shape of the mold.
[0084] Characterization of injectable and preformed materials method: Thermogravimetric analysis (TGA): Experiments were carried out on a NIETZSCH STA 409PC instrument on a thermomicrobalance under oxidizing atmosphere at a heating rate of 5°C / min from room temperature to 850°C.
[0085] Differential Scanning Calorimetry (DSC): Experiments were performed on a TA Q-20 machine. The heating rate was set at 5° C. / min, with temperatures ranging from 20° C. to 80° C. Approximately 20 mg pieces of material were weighed and placed in sealed aluminum pans. An empty sealed aluminum pan was used as a control.
[0086] Polarized Light Microscopy (PLM): The material was placed untreated between a glass slide and a cover slip. Observations were performed using a Zeiss AxioImager A2 POL in transmission. The microscope was equipped with standard accessories for the examination of birefringent samples under polarized light (i.e. crossed polarizers) and an AxioCam CCD camera.
[0087] Scanning electron microscopy (SEM): Samples were fixed in 2.5% glutaraldehyde solution. After washing with cacodylate / saccharose buffer solution, they were dehydrated through ethanol baths (30% to 100% ethanol). Supercritical CO2 drying was performed by a CPD-300 (Leica). Dried samples were cut into pieces, placed on a carbon tape covering a sample holder, and covered with a 15 nm gold layer. Observations were performed by using a Hitachi S-3400N microscope operating at 3 kV and 30 pA.
[0088] Considering the presence of water in the collagen microparticles (approximately 10%), the final composition of the material coincides with that of the initial mixture (Figure 1).
[0089] The denaturation temperature of collagen is about 48°C. This is close to the denaturation temperature reported for collagen gels (Tiktopulo, EI and Kajava, AV (1998) "Denaturation of type I collagen fibrils is an endothermic process accompanied by a noticeable change in the partial heat capacity", Biochemistry, 37(22), pp. 8147-8152), indicating that the addition of saline may promote fibrillogenesis. In fact, the denaturation temperature remains unchanged when fibrillogenesis is induced by ammonia vapor (calcified collagen gel). The addition of hydroxyapatite to a mixture of collagen microparticles and saline seems to induce favorable interactions: the denaturation enthalpy is higher and the width of the mid-height of the endotherm is less significant (Figure 2). This means that the addition of hydroxyapatite may tend to homogenize the collagen fibril (or microfibril) population.
[0090] As observed by PLM (Figure 3), the solution exhibits birefringent domains attesting to the anisotropy of the material, confirming that the addition of hydroxyapatite under these conditions does not interfere with the self-organization of collagen in the liquid crystalline phase.
[0091] This local anisotropy can also be seen by SEM through the observation of aligned mineralized collagen fibrils (Figure 4). Prior to fibrillogenesis, the material also shows partially dissolved collagen microparticles. The dissolution of the microparticles can be regulated by the mixing time before injection. After fibrillogenesis, more distinct fibrils are observed.
[0092] Example 2: Preformed composite material in 2 mM acetic acid (collagen / hydroxyapatite ratio 50:50) Preparation of preformed composite materials 40 mg of collagen powder obtained as disclosed herein above and 40 mg of hydroxyapatite powder obtained as disclosed herein above are mixed in a mortar. 0.15 mL of 2 mM acetic acid is added to the mortar. The whole is mixed for about 1 minute to obtain a homogeneous paste. The paste can be injected into the mold via a 1 mL syringe or spread on the mold with a spatula. Fibrillogenesis is carried out under ammonia vapor for 3 hours. The gel is then removed from the mold and rinsed with PBS until a neutral pH is reached. The material can then be implanted into the void that corresponds to the shape of the mold.
[0093] Characterization of preformed composites SEM observations show fibril aligned domains (Figure 5). The material appears dense.
[0094] SEM revealed areas of co-aligned collagen fibrils and hydroxyapatite nanoplatelets, similar to that observed in compact bone (Figure 6).
[0095] Example 3: Injection into the void - in vivo data The biocompatibility of the injectable collagen matrix was tested in an intramuscular position in rats. For this, a skin incision was made along the femoral axis and the fascia above the biceps femoris and gluteus muscles was incised. A gap was created between the two muscles and the material of Example 2 was inserted by injection. Thirty days after surgery, the rats were euthanized and the implanted material was extracted and analyzed. Histological thin sections stained with hematoxylin-eosin (Figure 7) showed both infiltration of immune cells and colonization by cells of mesenchymal lineage (fibroblasts or stem cells), confirming the malleability, simplicity and non-toxicity of the injectable material.
[0096] Example 4: Injectable and preformable materials (high-density collagen microparticles mixed with a biomimetic hydroxyapatite precursor solution) Preparation of the injectable composition 90 mg of collagen powder obtained as disclosed herein above was mixed with 1 mL of a biomimetic hydroxyapatite precursor solution obtained as disclosed herein (110 mM CaCl2·2H2O, 33 mM NaH2PO4 and 33 mM NaHCO3) in 500 mM acetic acid. The whole was mixed for about 1 minute to obtain a homogenous paste. The paste was transferred to an empty 1 mL syringe. The plunger was returned to its original position. The paste was then ready to be injected into the defect.
[0097] Preparation of preformed substrates The above protocol is repeated. The mixture is injected via a syringe into a silicone mold of the desired dimensions and a total volume of 1 mL. Fibril development (gelation) is carried out overnight under ammonia vapor. The gel is then removed from the mold and rinsed with saline until a neutral pH is reached. The material can then be implanted into the void that corresponds to the shape of the mold.
[0098] Characterization of preformed materials method: Scanning electron microscopy (SEM): Samples were fixed in 2.5% glutaraldehyde solution. After washing with cacodylate / saccharose buffer solution, they were dehydrated through ethanol baths (30% to 100% ethanol). Supercritical CO2 drying was performed by a CPD-300 (Leica). Dried samples were cut into pieces, placed on a carbon tape covering a sample holder, and covered with a 15 nm gold layer. Observations were performed by using a Hitachi S-3400N microscope operating at 3 kV and 30 pA.
[0099] Transmission electron microscopy (TEM): The protocol is similar to that for SEM. Samples were then rinsed, dehydrated and embedded in Epon 812. Sections (approximately 80 nm) were observed with a Tecnai spirit G2 operated at 120 kV.
[0100] Fourier transform infrared spectroscopy: Perkin Elmer Spectrum One spectrophotometer, 1 cm resolution -1 Fourier transform infrared spectra were obtained by attenuated total reflection.
[0101] SEM micrographs show that the material exhibits a high density of collagen fibrils (Figure 8a-c).
[0102] TEM micrographs show the alignment of collagen fibrils in the material (Figure 8d).
[0103] The infrared spectrum of the preformed material showed vibrational bands attributed to both collagen and apatite, thereby confirming the formation of a collagen mineralized matrix (Figure 8e).
[0104] [Example 5] Synthesis of composite collagen microparticles by aerosol The synthesis of collagen microparticles was carried out according to the procedures described by Nassif et al. (Paris, 2018. Injectable collagen suspensions, the preparation method thereof, and the uses thereof, particularly for forming dense collagen matrices. US Patent Application 15 / 558,787) and Lama et al. (Self-Assembled Collagen Microparticles by Aerosol as a Versatile Platform for Injectable Anisotropic Materials. Small, 1902224 pages, 2019). Moreover, salts present in the biomimetic hydroxyapatite precursor were added to the low-concentration collagen acidic collagen solution before atomization, resulting in the final composition: 2 mg / mL collagen, 500 mM acetic acid, 110 mM CaCl2·2H2O, 33 mM NaH2PO4 and 33 mM NaHCO3. The composition of the ionic precursor was modified to form composite collagen microparticles with different mineral / collagen ratios and to incorporate different therapeutic ions, e.g. Sr 2+ , Mg 2+ , Zn 2+ can be loaded.
[0105] For example, SrCl 2· 6H2O was added to the biomimetic hydroxyapatite precursor solution to form Ca 2+ 10%Sr 2+ (mol / mol) may be obtained.
[0106] Preparation of the injectable composition 90 mg of collagen powder obtained as disclosed herein above was mixed with 1 mL of 500 mM acetic acid. The whole was mixed for about 1 minute to obtain a homogenous paste. The paste was transferred to an empty 1 mL syringe. The plunger was replaced in its original position. The paste was then ready to be injected into the defect. Different weights of ions may be used to obtain different mineral / collagen ratios.
[0107] Preparation of preformed substrates The above protocol is repeated. The mixture is injected via a syringe into a silicone mold of the desired dimensions and a total volume of 1 mL. Fibril development (gelation) is carried out overnight under ammonia vapor. The gel is then removed from the mold and rinsed with saline until a neutral pH is reached. The material can then be implanted into the void that corresponds to the shape of the mold.
[0108] Characterization of preformed materials method: Energy dispersive X-ray spectroscopy (EDX) microanalysis: An EDX instrument X-Max (Oxford Instruments) was coupled to a Hitachi S-3400N scanning electron microscope operated at 12 kV, and the Oxford Microanalysis Group XAN.70 software was used for this analysis. Dry samples were cut into small pieces, placed on a carbon tape covering a sample holder, and covered with a 15 nm carbon layer.
[0109] Composite dense collagen / biomimetic hydroxyapatite precursor microparticles (Process 3).
[0110] As observed in the SEM micrographs, dense microparticles were formed (Figure 9 a).
[0111] EDX spectra confirm the incorporation of biomimetic hydroxyapatite precursors into the dense collagen microparticles (Figure 9b).
[0112] SEM images show a high density of fibrils in the preformed material produced using the composite dense collagen / biomimetic hydroxyapatite precursor microparticles (Figure 9c-d).
[0113] Example 6: Injectable composite material in 2 mM acetic acid (collagen / amorphous calcium phosphate ratio 30:70) Preparation of amorphous calcium phosphate Amorphous calcium phosphate powder is synthesized by atomization of a biomimetic hydroxyapatite precursor acidic solution of 110 mM CaCl2·2H2O, 33 mM NaH2PO4 and 33 mM NaHCO3 in 500 mM acetic acid using a spray processing technique as disclosed in WO2016 / 146954.
[0114] Preparation of preformed composite materials 40 mg of collagen powder obtained as disclosed herein above and 40 mg of amorphous calcium phosphate powder obtained as disclosed herein above are mixed in a mortar. 0.15 mL of 2 mM acetic acid is added to the mortar. The whole is mixed for about 1 minute to obtain a homogeneous paste. The paste can be injected into the mold via a 1 mL syringe or spread on the mold with a spatula. Fibrillogenesis is carried out under ammonia vapor for 3 hours. The gel is then removed from the mold and rinsed with PBS until a neutral pH is reached. The material can then be implanted into the void that corresponds to the shape of the mold.
Claims
1. - collagen microparticles containing more than 90% by weight of collagen; - a biomimetic hydroxyapatite or a biomimetic hydroxyapatite precursor or an amorphous calcium phosphate; and - Physiologically compatible aqueous solvent A composition comprising:
2. 2. The composition of claim 1, wherein the collagen microparticles are in the range of 0.05 to 20 μm in diameter as measured by electron microscopy or by dynamic light scattering.
3. The composition according to claim 1 or 2, wherein the collagen microparticles are type I collagen microparticles.
4. The composition according to any one of claims 1 to 3, wherein the physiologically compatible aqueous solvent is physiological serum, phosphate buffer, sodium bicarbonate or blood.
5. The composition of any one of claims 1 to 4, wherein the composition further comprises one or more therapeutic or bioactive agents.
6. 6. The composition according to any one of claims 1 to 5, wherein the weight ratio of collagen microparticles to biomimetic hydroxyapatite or amorphous calcium phosphate is in the range of 10:90 to 90:10, preferably 30:70 to 80:20, more preferably 50:
50.
7. The composition of any one of claims 1 to 6, wherein the composition is injectable or implantable.
8. A composition according to any one of claims 1 to 7 for use in the repair and regeneration of calcified tissue.
9. The composition according to claim 8 for bone repair and regeneration.
10. A composition according to any one of claims 1 to 7 for inducing new bone formation, promoting bone growth and / or treating bone defects.
11. A composition according to any one of claims 1 to 7 for use in bone reconstruction procedures, preferably in the repair of bone defects in maxillofacial or orthopedic surgery.
12. A preformed implantable matrix comprising the composition of any one of claims 1-7.
13. A process for preparing a composition according to any one of claims 1 to 7, comprising the steps of: (a) providing collagen microparticles comprising greater than 90% by weight collagen; (b) providing a biomimetic hydroxyapatite powder or an amorphous calcium phosphate powder; (c) mixing the collagen microparticles with the hydroxyapatite powder or the amorphous calcium phosphate powder; and (d) adding a physiologically compatible aqueous solvent; A process including.
14. A process for preparing a composition according to any one of claims 1 to 7, comprising the steps of: (a) atomizing an acidic solution containing undenatured and uncrosslinked collagen and a biomimetic hydroxyapatite precursor; (b) adding a physiologically compatible aqueous solvent to the particles obtained in step (a); A process including.
15. A process for preparing a composition according to any one of claims 1 to 7, comprising the steps of: (a) providing collagen microparticles comprising greater than 90% by weight collagen; (b) adding a physiologically compatible aqueous solvent containing a biomimetic hydroxyapatite precursor to the collagen microparticles. A process including.
Citation Information
Patent Citations
Organic hard tissue-like hardened substance, powder composition and their use
JP2003093496A
Powdery apatite / collagen complex, shape-formable artificial bone paste, and method for producing them
JP2009261726A
Methods and compositions to graft bone using iron excipients
US20220016312A1